Analysis of the Activities of “Science Journal of Volgograd State University. History. Area Studies. International Relations” for 10 Years (2014–2023) - Vitaliy Gorelkin; Natalia Rybalko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. “Science journal of Volgograd State University. History. Area Studies. International Relations” has been published 6 times a year since 2014, and since the second half of 2015, it has had a new editorial board and editorial staff under the leadership of Chief Editor, Doctor of Sciences (History), Professor Igor Olegovich Tyumentsev. The purpose of the article is to trace the quantitative and qualitative changes that have occurred over the ten-year period of the journal’s activity and to identify the main achievements of the journal. Methods and Materials. The study is based on the materials of 60 issues of the journal for the period from 2014 to 2023; descriptive, comparative and quantitative methods of analysis were used. Analysis. The analysis of the main stages of the journal’s development related to changes in strategy, renewal of the editorial board and editorial staff, and inclusion of the journal in international citation databases was conducted. The article presents statistics on the number and volume of published articles, the composition of authors taking into account their territorial affiliation, the composition of the reviewer pool, the number of citations of the journal, the distribution of articles by scientific direction and subject. Results. It was possible to show the place of the journal in the national and international rankings, the degree of integration of the journal into the international scientific space, and the positive dynamics of development. A direct connection was traced between the achievements of the journal and the main factors contributing to this: active joint work of the editorial staff and the editorial board, financial support from the Volgograd State University, the transition to a parity release of thematic and non-thematic issues, and tightening of requirements for the quality of articles and reviewing. Authors’ contribution. N.V. Rybalko prepared the sections “Introduction” and “Historiography” and, analyzed changes in the composition of the editorial staff of the journal and the quantitative and regional composition of authors and reviewers. V.A. Gorelkin described the development strategy of the journal and presented an analysis of indexing, citation, journal ratings, and publication topics. The remaining sections were written jointly.